Indoor Outdoor Relationship Of Fine Particles (PM2.5) IN School Classroom - Kamaruddin, Muhamad Al-Amin (Universiti Sains Malaysia, 2017)
People spend about 90 % of their lifetime indoors and indoor air pollution is one of the most harmful environmental factors for human health. Studies have shown that there is significant relationship between indoor air quality (IAQ) status with surrounding activities. In this study, PM2.5 concentration was monitored during teaching and learning session from 8.00 a.m. to 2.00 p.m. at two primary schools exposed to different major expected sources that are industry (Sekolah Kebangsaan Sungai Kechil) and mobile (Sekolah Kebangsaan Khir Johari) sources. The effect of building design towards the intrusion of outdoor PM2.5 into the indoor air quality in classroom was investigated. In each school, two rooms have been selected based on the type of window that is installed in a room with a window that uses a louvre and sliding window. The average of PM2.5 concentration in classroom with louvre window (CLW) and classroom with sliding window (CSW) were obtained which for SK Sungai Kechil (value for CLW and CSW) were 13 μg/m³ and 35 μg/m³ while for SK Khir Johari (value for CLS and CSW) were 27 μg/m³ and 37 μg/m³. Results shows that there exist statistically significant differences (p-value <0.05) of parameter indoor and outdoor PM2.5 concentration between these two schools. As a conclusion, the influence from the surrounding activities and indoor sources are important in contributing on indoor concentrations of pollutants in school classroom.